Effect Of Allium Sativum Aqueous Extract On Egg Load And Worm Burden In Immunosuppressed Guinea Pigs Infected With Schistosoma Haematobium (Applied Biological Research, 2013)
Current research was designed to evaluate the prophylactic and therapeutic  potential of garlic (Allium sativum) aqueous extracts in Schistosoma  haematobium infection, using immuno-suppressed guinea pigs as animal  model. Twenty four infected male guinea pigs were divided into various  groups that were treated with A. sativum extracts over different periods,  praziquantel treated group and control. Eggs recovered in various groups were counted and recorded. A substantial reduction in egg load of S.  haematobium was observed in A. sativum extract-treated and praziquantel  treated groups in comparison to untreated control. Further, praziquantel and  sativum extract treatments significantly reduced worm burden. S.  haematobium infection was established in guinea pigs under controlled  immunosuppression. The study suggests that A. sativum aqueous extract is a  convenient prophylactic and promising therapeutic agent for the control of S.  haematobium infection.
Keywords: Allium sativum; guinea pig; praziquantel; prophylactic potential; Schistosoma haematobium